A study on factors that affecting employee retention among production employees in Hino Motors Manufacturing Malaysia Sdn Bhd (HMMMSB) / Izzah Izzati Mahpuz and Nur Hidayah Ramli - Mahpuz, Izzah Izzati; Ramli, Nur Hidayah (Faculty of Business and Management, 2016)
Employee Retention refers to the ability of the organization to retain its employees and it's emerging as a big challenge to organizations. Organization commitment, job satisfaction and compensation highly influence the retention rate in Hino Motors Manufacturing (Malaysia) SDN BHD. The study was conducted to find out potential reasons for an employee to leave his job and also help the organization to handling the problems faced by an organization with the high employee turnover. In addition, the results revealed that the most influential factors that affecting employee retention in Hino Motors Manufacturing (Malaysia) SDN BHD is organizational commitment. The implication of this research hopefully will make contribution to the all industries, employees and employers in attempted to handling employee retention issues and understand the relationship between the factors that lead to employee retention and together fostering it in achieving common goals.